Exploratory disproportionality analysis of potentially drug-induced eosinophilic pneumonia using United States Food and Drug Administration adverse event reporting system - Ashwin Kamath (Scientific Reports)
Abstract Drug-induced eosinophilic pneumonia (EP) is an uncommon adverse drug reaction. Many drugs have been reported to cause EP, the evidence mainly being in the form of case reports/case series. This study aims to conduct an exploratory analysis of the United States Food and Drug Administration adverse event reporting system (FAERS) database to identify previously unknown drugs that can cause EP and supplement the available evidence for known culprit drugs. A retrospective case–noncase study was conducted using individual case safety reports (ICSRs) reported to the US FAERS from the first quarter of 2004 to the second quarter of 2024. Cases of potentially drug-induced EP were identified using OpenVigil application by conducting a narrow and broad scope search using the Medical Dictionary of Regulatory Activities preferred terms. A base list of drugs described in select literature to have caused EP was used to categorize known and unknown drugs. A disproportionality analysis was performed, with a reporting odds ratio > 2, lower end of the 95% confidence interval > 1, and a minimum of 3 reported cases considered a signal of disproportionate reporting (SDR). During the study period, 8,702,548 individual case safety reports (ICSRs) were submitted to the FAERS. Of these, 855 ICSRs using the narrow scope search and 1411 ICSRs using the broad scope search reported EP. The three most commonly reported drugs with an SDR for EP using the narrow scope search were daptomycin, naltrexone, and prednisone. The most common indications for the use of the drugs were infections, immunological conditions, asthma, and central nervous system disorders. In total, there were 45 drugs with an SDR but no supporting literature evidence available. The number of drugs implicated in causing EP has increased over the years. Several antimicrobial agents, followed by drugs affecting the central nervous system and anticancer drugs, including monoclonal antibodies, can produce EP. The list of suspected drugs identified in this study, especially those with SDR and literature evidence, should be strongly considered as a possible cause in patients presenting with pneumonia not explained otherwise.